Design, analysis and fabrication mini sander belt machine / Muhammad Bariq Mohd Bakhit - Mohd Bakhit, Muhammad Bariq (2024)
A machine is equipment that is created to make work easier. It is a tool that amplified the effect of human effort. Currently, there are a lot of available machines in the market which comes in every size and prize. The problem with machines nowadays is it expensive and hard to get the mini size. Thus, this project was carried out with the objective of designing and fabricating a mini electrical sander belt. The machine will go through a design process using SOLIDWORKS and fabricated using drilling, cutting, and grinding process. The materials that will be used are aluminum. The possible outcome should be by turning on the switch, the sander belt will start operating and can be used for the grinding process of the small item like shaping the knife and reshaping the drill bit. It is concluded the expected mini machine will be a lot more useful for small projects and affordable for most users